2002
DOI: 10.1038/sj.bjc.6600610
|View full text |Cite
|
Sign up to set email alerts
|

Induction of vasculogenesis in breast cancer models

Abstract: Recently, there have been reports of postnatal vasculogenesis in cases of ischaemia models. The aim of the present study is to provide evidence of postnatal vasculogenesis in breast-cancer -bearing mice. Based on cell surface antigen expression, we isolated endothelial precursor cells from bone marrow, peripheral blood and tumour-infiltrating cells from mice that had received six human breast cancer xenografts. In all three areas (bone marrow, peripheral blood and tumour-infiltrating cells), endothelial precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…16,26,27,38,66,72,81 VM has been also described in experimental and spontaneous malignant breast cancer. 4,36,58,[60][61][62][63] To our knowledge, there are no previous studies of VM in spontaneous animal tumors, including canine mammary tumors and IMC.…”
Section: Discussionmentioning
confidence: 99%
“…16,26,27,38,66,72,81 VM has been also described in experimental and spontaneous malignant breast cancer. 4,36,58,[60][61][62][63] To our knowledge, there are no previous studies of VM in spontaneous animal tumors, including canine mammary tumors and IMC.…”
Section: Discussionmentioning
confidence: 99%
“…These cells originate in the bone marrow, can be detected in the peripheral circulation and are incorporated into sites of ongoing angiogenesis where they differentiate into mature endothelial cells (Asahara et al 1997, Lyden et al 2001. VEGF has a potential role in such recruitment and there is evidence for EPC recruitment in breast cancer cells (Asahara et al 1999, Shirakawa et al 2002a,b, Spring et al 2005. It has been reported that EPCs decline after treatment with antiangiogenic therapy (Capillo et al 2003) thus making these cells targets for such therapy (Rafii et al 2002).…”
Section: Potential Sex-steroid Targets For Anti-angiogenic Therapy Ofmentioning
confidence: 99%
“…Human umbilical vascular endothelial cells (HUVECs) grown on Matrigel form a capillary-like tube network in an MMP-dependent manner. [30][31][32] Thus, the effect of 2d and 2g on the tube formation of HUVECs was analyzed. Tube formation of VEGF (10 ng/mL)-treated HUVECs was dose-dependently inhibited by 2d and 2g similar to the inhibition by BB-94 (Fig.…”
Section: Resultsmentioning
confidence: 99%